2003
DOI: 10.1124/jpet.102.046870
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Oral Morphine Antinociceptive Tolerance and Naloxone-Precipitated Withdrawal Signs by Oral Δ9-Tetrahydrocannabinol

Abstract: Previous studies have demonstrated a functional interaction between cannabinoid and opioid systems in the development and expression of morphine tolerance and dependence. In these experiments, we examined the effect of a low oral dose of ⌬ 9 -tetrahydrocannabinol (⌬ 9 -THC) on the development of oral morphine tolerance and the expression of naloxone-precipitated morphine withdrawal signs of jumping and diarrhea in ICR mice. Chronic treatment with high-dose oral morphine produced a 3.12-fold antinociceptive tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
70
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 25 publications
4
70
2
1
Order By: Relevance
“…However, the present study did not assess the full dose-response relationship of these drugs in combination to infer whether these drugs offer protection against one another's side effects. Interestingly, other studies demonstrated that THC, as well as fatty acid amide hydrolase inhibitors and MAGL inhibitors, block opioid withdrawal somatic signs (Cichewicz and Welch, 2003;Ramesh et al, 2011Ramesh et al, , 2013. The present results suggest that a low dose of MJN110 and morphine in combination produced enhanced antinociception, while decreasing the likelihood of at least some untoward side effects.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…However, the present study did not assess the full dose-response relationship of these drugs in combination to infer whether these drugs offer protection against one another's side effects. Interestingly, other studies demonstrated that THC, as well as fatty acid amide hydrolase inhibitors and MAGL inhibitors, block opioid withdrawal somatic signs (Cichewicz and Welch, 2003;Ramesh et al, 2011Ramesh et al, , 2013. The present results suggest that a low dose of MJN110 and morphine in combination produced enhanced antinociception, while decreasing the likelihood of at least some untoward side effects.…”
Section: Discussionsupporting
confidence: 56%
“…In current times, preclinical studies have established that the combination of opiates and cannabinoids produce enhanced antinociceptive effects. Coadministration of the primary psychoactive component of marijuana, D 9 -tetrahydrocannabinol (THC) (Gaoni and Mechoulam, 1964), and morphine produces synergistic antinociceptive effects in acute pain tests (Cichewicz and Welch, 2003) and in the rat Freund's complete adjuvantinduced arthritic model (Cox et al, 2007). Additionally, the potent synthetic cannabinoid receptor agonist CP55,940 produces a leftward shift of the morphine dose response curve in the acetic acid abdominal stretching pain assay (Miller et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cannabinoids also potentiate the analgesic effects of morphine and prevent tolerance. [4,5] These desirable effects of cannabinoids show promise for management of cancer pain and may lead to improved analgesic therapy. Mean percent change in paw withdrawal threshold relative to baseline reading prior to SCC or sham inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the antinociceptive potency of cannabinoids is decreased in morphine-tolerant monkeys (Gerak et al, 2015) and in some morphine-tolerant rats (Basilico et al, 1999;Yesilyurt and Dogrul, 2004;Maguma and Taylor, 2011). When opioids and cannabinoids are combined, tolerance and cross-tolerance might develop concurrently and produce a greater decrease in antinociceptive potency than would be observed when either drug is given alone; however, some studies in rodents receiving morphine and cannabinoids concurrently report that antinociceptive tolerance is not greater for the combination (Cichewicz and Welch, 2003;Smith et al, 2007;Fischer et al, 2010). The goal of the current study was to determine whether THC alters tolerance to and dependence on morphine in monkeys.…”
mentioning
confidence: 99%